Solomon Islands : Request for an Arrangement Under the Standby Credit Facility; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Solomon Islands. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The effects of the global recession and decline in logging have undermined macroeconomic stability in the Solomon Islands. The government's program offers a basis for resuming strong growth in a low inflation environment, helping to advance poverty alleviation efforts and achieve other development objectives. The current monetary policy stance is broadly appropriate, with monetary targets sufficiently accommodative to support economic recovery. Sound steps toward strong financial sector policy have been taken. The program, while not without risk, is well focused and sufficiently ambitious.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet